PENERAPAN MODEL REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR PADA MATA PELAJARAN MATEMATIKA - Nope, Marlin (2016)
This research is motivated by the lack of student learning outcomes SDN IIIA class I 1 in mathematics consequences for teachers implementing learning to use the lecture method without props manipulative or concrete objects. Generally, this study aims to describe the application of the model Realistic Mathematic Education to improve student learning outcomes SDN I IIIA class in mathematics matter of addition and subtraction and multiplication three-digit numbers that hasinya three points. Specifically purpose of this study was to describe the planning, implementation and improvement of student learning outcomes in mathematics material addition and subtraction of three digit numbers by applying the model RME. The method used in this study is a classroom action research (PTK) and Mc Kemmis models. Taggart. Data collected through tests, observation and documentation. His research is class III A totaling 34 people. The results showed that the application of the model RME in mathematics learning need to be planned carefully. Application of this model was found to increase the activity and student learning outcomes in mathematics matter of addition and subtraction and multiplication three-digit numbers are the result of three figures. Evident from the average value and the percentage of achievement of KKM increased. In the first cycle the average value reached 62.06 with a percentage of 67.65%. In the second cycle increased with the average value reached 87.94 with a percentage of 97.06%.;--- Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar siswa kelas IIIA SDN I 1 pada mata pelajaran matematika berakibat karena guru melaksanakan pembelajaran dengan menggunakan metode ceramah tanpa alat peraga manipulatif atau benda-benda konkrit. Secara umum penelitian ini bertujuan mendeskripsikan penerapan model Realistic Mathematic Educationuntuk meningkatkan hasil belajar siswa kelas IIIA SDN I pada mata pelajaran matematika materi penjumlahan dan pengurangan bilangan tiga angka dan perkalian yang hasinya tiga angka. Secara khusus tujuan penelitian ini adalah untuk mendeskripsikan perencanaan, pelaksanaan dan peningkatan hasil belajar siswa pada mata pelajaran matematika materi penjumlahan dan pengurangan bilangan tiga angka dengan menerapkan model RME. Metode yang digunakan dalam penelitian ini adalah metode penelitian tindakan kelas (PTK) model Kemmis dan Mc. Taggart. Pengumpulan data dilakukan melalui tes, observasi, dan studi dokumentasi. Subjek penelitiannya adalah siswa kelas IIIA yang berjumlah 34 orang. Hasil penelitian menunjukan bahwa penerapan model RME dalam pembelajaran matematika perlu direncanakan secara cermat. Penerapan model ini ternyata dapat meningkatkan aktivitas dan hasil belajar siswa pada mata pelajaran matematika materi penjumlahan dan pengurangan bilangan tiga angka dan perkalian yang hasilnya tiga angka. Terbukti dari nilai rata-rata dan persentase pencapaian KKM yang meningkat. Pada siklus I nilai rata-rata mencapai 62,06 dengan persentase 67,65%. Pada siklus II mengalami peningkatan dengan nilai rata-rata mencapai 87,94 dengan persentase 97,06%.